ZASADA WIERNOŚCI BOGU I CZŁOWIEKOWI W ORGANIZACJI ŚWIATOWYCH DNI MŁODZIEŻY – ZARYS PROBLEMATYKI - Kopiczko, Tomasz (Studia Katechetyczne, 2016)
The principle of being faithful to God and a human is one of the main pastoral principles. The aim of this article is pointing that The World Youth Days are a phenomenon that provides understanding and accomplishing this principle. The World Youth Days are international meetings of young people from all over the world who gather in one place to make a confession of faith in Jesus Christ. They arose out of the concern of John Paul II who was tireless to wander The Earth to look for young people and faced them with his paternal love. As a result, these meetings have brightened young people’s faith for30 years. Neither documents nor decrees would guarantee such newness of faith, but only real and personal meeting a human and God. The subsequent popes ant the entire organization structure wants to show young people God and His way of acting in the world and human life.